2017
DOI: 10.1101/237586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Firefly genomes illuminate parallel origins of bioluminescence in beetles

Abstract: SummaryFireflies are among the best-studied of the bioluminescent organisms. Despite longterm interest in the biochemistry, neurobiology, and evolution of firefly flash signals and the widespread biotechnological applications of firefly luciferase, only a limited set of genes related to this complex trait have been described. To investigate the genetic basis of firefly bioluminescence, we generated a high-quality reference genome for the Big Dipper firefly Photinus pyralis, from which the first laboratory luci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 254 publications
(226 reference statements)
4
70
1
Order By: Relevance
“…These differences could reflect divergence of a common luciferase, or convergent evolution of two or more distinct ancestral enzymes to achieve light emission with d ‐luciferin. Complete genomes for different bioluminescent beetle species are now available, and analysis of these genomes adds credence to the latter theory: The luciferases for fireflies and click beetles both arose from separate duplication events of ancestral ACSLs, which independently converged on luciferase activity with d ‐luciferin .…”
Section: Fireflies and Related Beetles Evolved Luciferases From Fattymentioning
confidence: 98%
See 3 more Smart Citations
“…These differences could reflect divergence of a common luciferase, or convergent evolution of two or more distinct ancestral enzymes to achieve light emission with d ‐luciferin. Complete genomes for different bioluminescent beetle species are now available, and analysis of these genomes adds credence to the latter theory: The luciferases for fireflies and click beetles both arose from separate duplication events of ancestral ACSLs, which independently converged on luciferase activity with d ‐luciferin .…”
Section: Fireflies and Related Beetles Evolved Luciferases From Fattymentioning
confidence: 98%
“…recently demonstrated that l ‐luciferin can be synthesized in neutral buffer conditions under air atmosphere at room temperature, enzymes likely mediate in vivo d ‐luciferin metabolism . To establish the identities of the enzymes responsible for luciferin metabolism, recent studies have focused on characterization of the transcriptome of fireflies . These studies have uncovered several candidate enzymes that could presumably function in these reactions and have high expression in lantern tissue .…”
Section: Biosynthesis Of D‐luciferinmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome profiling revealed multiple conserved genes that are likely involved in the de novo synthesis of D-luciferin. [13] Related efforts to elucidate coelenterazine biosynthesis have also been reported. [14]…”
Section: Discovering New Luciferases and Luciferinsmentioning
confidence: 99%